Survival Analysis of Diabetic Colorectal Cancer Patients on Metformin - Alex Brandon Wong; Ravi Patnaik; Li Ling Chaw; Shir Kiong Lu; Long Chiau Ming; Wen Han Chooi; Ya Chee Lim (Progress in Microbes and Molecular Biology)
Metformin, an antihyperglycemic drug, has been associated with antineoplastic effects and could potentially improve colorectal cancer prognosis. The association between metformin and colorectal cancer prognosis has shown conflicting results. This study aims to define the association between metformin and colorectal cancer prognosis in colorectal cancer patients in the Brunei population. The study was a retrospective cohort study that included colorectal cancer patients from The Brunei Cancer Center (TBCC) treated between July 2014 and July 2019. Kaplan-Meier and multivariate Cox proportional hazard regression models were used to analyze the data, construct survival curves, and adjust for comorbidities. Of a total of 112 diabetic patients, 79 patients (70.5%) were on metformin, and 33 patients (29.5%) were on other antihyperglycemic medications. An association between metformin use and lower incidence of stage IV colorectal cancer (p = 0.046) was observed, but no significant difference between the metformin group and the non-metformin group in terms of survival probability (log rank p = 0.13) was shown. Analysis using multivariate models showed that metformin reduces the hazard ratio by 31.2%, although this value is statistically insignificant (HR, 0.688; 95% CI 0.286 – 1.654; p = 0.403). Among the diabetic colorectal cancer patients, there was no association between survival and metformin therapy. However, the association between cancer progression and metformin use requires further investigation, and high-powered clinical trials are needed to support these findings.